Are general practice characteristics predictors of good glycaemic control in patients with diabetes? A cross‐sectional study. Issue 1 (18th January 2016) - Esterman, Adrian J; Fountaine, Tim; McDermott, Robyn
Abstract: Objectives: To determine whether certain characteristics of general practices are associated with good glycaemic control in patients with diabetes and with completing an annual cycle of care (ACC). Research design and methods: Our cross‐sectional analysis used baseline data from the Australian Diabetes Care Project conducted between 2011 and 2014. Practice characteristics were self‐reported. Characteristics of the patients that were assessed included glycaemic control (HbA1c level ≤ 53 mmol/mol), age, sex, duration of diabetes, socio‐economic disadvantage (SEIFA) score, the complexity of the patient's condition, and whether the patient had completed an ACC for diabetes in the past 18 months. Clustered logistic regression was used to establish predictors of glycaemic control and a completed ACC. Results: Data were available from 147 general practices and 5455 patients with established type 1 or type 2 diabetes in three Australian states. After adjustment for other patient characteristics, only the patient completing an ACC was statistically significant as a predictor of glycaemic control ( P = 0.011). In a multivariate model, the practice having a chronic disease‐focused practice nurse ( P = 0.036) and running educational events for patients with diabetes ( P = 0.004) were statistically significant predictors of the patient having complete an ACC. Conclusions: Patient characteristics are moderately good predictors of whether the patient is in glycaemic control, whereas practice characteristics appear to predict only the likelihood of patients completing an ACC. The ACC is an established indicator of good diabetes management. This is the first study to report a positive association between having completed an ACC and the patient being in glycaemic control.